1985
DOI: 10.1111/j.1476-5381.1985.tb09431.x
|View full text |Cite
|
Sign up to set email alerts
|

The positive inotropic action of the nifedipine analogue, Bay K 8644, in guinea‐pig and rat isolated cardiac preparations

Abstract: 1 The inotropic effect of Bay K 8644 has been studied in rat and guinea-pig atria and ventricular strips stimulated at I Hz, in a medium containing CaC12 1.8 mM. The positive inotropic effect at maximal effective concentrations of Bay K 8644 was in the following order: guinea-pig ventricle > rat ventricle > guinea-pig atria >> rat atria. 2 In rat preparations, the tension recorded at maximum effective concentrations of Bay K 8644 was similar at three different calcium concentrations (0.7, 1.8, 3.0mM). The ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The Ca agonist Bay K 8644 (Schramm et al, 1983) produces a positive inotropic effect in rat ventricular strips (Finet et al, 1985), and we studied the effect of EIPA on the responses induced by 10 nM and 0.3 giM Bay K 8644. This latter concentration produced a maximal inotropic effect.…”
Section: Resultsmentioning
confidence: 99%
“…The Ca agonist Bay K 8644 (Schramm et al, 1983) produces a positive inotropic effect in rat ventricular strips (Finet et al, 1985), and we studied the effect of EIPA on the responses induced by 10 nM and 0.3 giM Bay K 8644. This latter concentration produced a maximal inotropic effect.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in agreement with the observation made by Vaghy. et al (1984) that Bay K 8644 and nitrendipine share the same binding sites and with the studies of Schramm et al (1983b), Yamamoto et al (1984), Spedding & Berg (1984), Kanmura et al (1984), Spedding (1985) and Finet et al (1985) which demonstrated a reversible antagonism between Bay K 8644 and other dihydropyridines (nifedipine, nisoldipine, dazopidine) on different preparations.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, in our experiments on the guinea-pig trachea and on the human bronchus, as in those performed on the rabbit aorta (Schramm et al, 1983a,b;Yamamoto et al, 1984), on the guinea-pig caecum (Spedding & Berg, 1984) and on the isolated heart of dog (Vaghy et al, 1984), guinea-pig (Schramm et al, 1983,b;Finet et al, 1985) or rat (Finet et al, 1985) Bay K 8644 exerted a contractile effect in a K+-enriched medium. This effect was competitively inhibited by nicardipine, a dihydropyridine derivative.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated in several studies that dihydropyridine Ca2" channel activators (Bay K 8644, CGP28392, the (+)-isomer of 202-791) increase depolarization-induced uptake of45Ca2' and release of [3H]-noradrenaline, increase the V.. of the slow response action potential and enhance myocardial contractility and calcium current (Schramm et al, 1983;Erne et al, 1984;Thomas et al, 1984;1985;Renaud et al, 1984;Brown et al, 1984;Hess et al, 1984;Finet & Godfraind, 1985;Kongsamut et al, 1985;Dube et al, 1985;Schramm & Towart, 1985). The present experiments were undertaken to determine whether stimulation of transmembrane Ca2+-entry by the light-stable activator, CGP 28392 (CGP) (Truog et al, 1984) could affect the anomalous forcefrequency relationship in rat myocardium (Langer, 1978), since it is thought that the phenomenon may be causally related to the deficiency of transmembrane Ca2" influx in this species (Nawrath, 1980).…”
Section: Introductionmentioning
confidence: 99%